PROTECTIVE EFFECT OF SYNTHETIC ANTIOXIDANTS AND ETHANOLIC EXTRACT OF BACOPA MONNIERI AGAINST LEAD TOXICITY INDUCED METABOLIC DYSFUNCTIONS IN MICE BRAIN AND LIVER HOMOGENATES: AN IN VITRO APPROACH - FLORA C SHAH; NAYAN K JAIN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objective of the present study was to investigate the ameliorative potential of synthetic antioxidants mixture comprising N-acetyl cysteine, ascorbic acid, tocopheryl acetate, and thiamine as micronutrient combinational therapy and ethanolic extract of Bacopa monnieri as herbal antioxidant therapy approach against lead toxicity-induced metabolic dysfunctions in vitro. Methods: Experimental study involved in vitro exposure of mice brain and liver homogenates to different doses (100 μM, 250 μM, and 500 μM) of lead acetate. The study also involved coadministration of high-dose lead acetate (500 μM) and specific dosage of synthetic antioxidants or ethanolic extract of B. monnieri separately to homogenate cultures. Alterations in metabolic parameters of protein levels and lipid peroxidation were analyzed for evaluating the protective effect of synthetic antioxidants and B. monnieri against lead intoxication. Results: Results revealed dose-dependent statistically significant (p<0.001) reduction in protein levels and elevation in lipid peroxidation in lead acetate exposed mice brain and liver homogenates as compared to their respective control groups. Coadministration of lead acetate and synthetic antioxidants mixture or B. monnieri in the brain and liver homogenates conferred protection and manifested maintenance of studied biochemical parameters nearest to control groups. Ameliorative efficacy of B. monnieri against lead-induced neurotoxicity and hepatotoxicity was found to be more pronounced than that of a mixture of synthetic antioxidants. Conclusion: Synthetic antioxidants mixture (N-acetyl cysteine, ascorbic acid, tocopheryl acetate, and thiamine) and B. monnieri exhibited remarkable therapeutic efficacy against lead toxicity-induced metabolic dysfunctions in mice brain and liver homogenates by virtue of their antioxidant, neuroprotective, and hepatoprotective abilities.